Answer:
See the answers below
Explanation:
Nine
The first step is to find the common difference. That's found by using
Common Difference
t4 - t3
t4 = - 15
t3 = - 19
t4 - t3 = -15 - - 19
t4 - t3 = -15 + 19
t4 - t3 = 4
t1 = - 27 which is the first term.
Explicit formula
tn = a + (n - 1)*d
tn = - 27 + (n - 1)*4
t5 = -27 + (5 - 1)*4
t5 = -27 + 4*4
t5 = - 11
Recursive
tn = tn - 1 + 4
Ten
Common difference
t4 - t3
21 - 15
Common difference = 6
t2 = 33 - 6
t2 = 27
Explicit formula
tn = a + (n - 1)*d
tn = 33 + (n - 1)*6
Recursive Formula
tn = tn-1 + 6
There are too many answers between the 2 questions that the exact format can be followed and have it make sense. You are better off following each question and writing down the answers as you come to them.